Teacher education and inclusion in Ghana : pre-service teachers' preparedness for creating an inclusive classroom - Nketsia, William (2011)
Education of pupils with special education needs (SENs) in Ghana has been formed around the medical model where pupils with special needs are diagnosed, labelled and taught in segregated special education institutions disconnected from regular mainstream classroom (Hooker, 2008). Recently, there has been increased focus on the adoption of inclusive education (IE) which seeks to reinforce the competence and efficiency of systems in school to reach out to all learners. Therefore, it is important for regular classroom teachers to be trained in the identification and support of the pupils with SENs in order for them to address the needs of all students. Recent studies in Ghana have concentrated on the perception of teachers towards IE and factors impeding its implementation (Agbenyega 2003; Desai & Kuyini 2006). Inadequate training of teachers is one of factors identified; however, they failed to describe the extent of pre-service teachers’ knowledge on the concepts of IE, SENs and instructional strategies for its effective implementation and these were the main objectives for this study. Although, respondents from 200 final year pre-service teachers in three Colleges of Education confirmed the findings of Opoku-Inkoom (2009) that majority of pre-service teachers are knowledgeable of some of the basic concepts of IE and SENs, however, almost half of the respondents demonstrated less knowledge and few of the participants could actually put their knowledge on these concepts into practice. Therefore, the study concluded that full course on inclusive education should be made compulsory for final pre-service teachers couple with a well-planned teaching practice in an inclusive setting to enhance their practical knowledge, skills and attitudes.